Loose-patch clamp analysis applied to voltage-gated ionic currents following pharmacological ryanodine receptor modulation in murine hippocampal cornu ammonis-1 pyramidal neurons - Bertagna, Federico; Ahmad, Shiraz; Lewis, Rebecca; Silva, S. Ravi P.; McFadden, Johnjoe; Huang, Christopher L.-H.; Matthews, Hugh R.; Jeevaratnam, Kamalan (Frontiers in Physiology, 2024)
Introduction The loose-patch clamp technique was first developed and used in native amphibian skeletal muscle (SkM), offering useful features complementing conventional sharp micro-electrode, gap, or conventional patch voltage clamping. It demonstrated the feedback effects of pharmacological modification of ryanodine receptor (RyR)-mediated Ca2+ release on the Na+ channel (Nav1.4) currents, initiating excitation–contraction coupling in native murine SkM. The effects of the further RyR and Ca2+-ATPase (SERCA) antagonists, dantrolene and cyclopiazonic acid (CPA), additionally implicated background tubular-sarcoplasmic Ca2+ domains in these actions. Materials and methods We extend the loose-patch clamp approach to ion current measurements in murine hippocampal brain slice cornu ammonis-1 (CA1) pyramidal neurons. We explored the effects on Na+ currents of pharmacologically manipulating RyR and SERCA-mediated intracellular store Ca2+ release and reuptake. We adopted protocols previously applied to native skeletal muscle. These demonstrated Ca2+-mediated feedback effects on the Na+ channel function. Results Experiments applying depolarizing 15 ms duration loose-patch clamp steps to test voltages ranging from −40 to 120 mV positive to the resting membrane potential demonstrated that 0.5 mM caffeine decreased inward current amplitudes, agreeing with the previous SkM findings. It also decreased transient but not prolonged outward current amplitudes. However, 2 mM caffeine affected neither inward nor transient outward but increased prolonged outward currents, in contrast to its increasing inward currents in SkM. Furthermore, similarly and in contrast to previous SkM findings, both dantrolene (10 μM) and CPA (1 μM) pre-administration left both inward and outward currents unchanged. Nevertheless, dantrolene pretreatment still abrogated the effects of subsequent 0.5- and 2-mM caffeine challenges on both inward and outward currents. Finally, CPA abrogated the effects of 0.5 mM caffeine on both inward and outward currents, but with 2 mM caffeine, inward and transient outward currents were unchanged, but sustained outward currents increased. Conclusion We, thus, extend loose-patch clamping to establish pharmacological properties of murine CA1 pyramidal neurons and their similarities and contrasts with SkM. Here, evoked though not background Ca2+-store release influenced Nav and Kv excitation, consistent with smaller contributions of background store Ca2+ release to resting [Ca2+]. This potential non-canonical mechanism could modulate neuronal membrane excitability or cellular firing rates.